Jim Henson's The power of the Dark Crystal. - Spurrier, Simon; Johnson, Phillip Kennedy, 1970- (Jim Henson's The Power of the Dark Crystal ;, 2017)
As Thurma and Kensho continue on their journey together, Jen is in hot pursuit, rediscovering the world he's ruled and neglected.